Retraction Note: Is early intervention using Mansoura-VV uterine compression sutures an effective procedure in the management of primary atonic postpartum hemorrhage? : a prospective study - Abd Elaziz A. El Refaeey; Hosam Abdelfattah; Alaa Mosbah; Anas M. Gamal; Emad Fayla; Waleed Refaie; Abdelhady Zaied; Rafik I. Barakat; Amal K. Seleem; Mohammed Maher (BMC, 2023)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12884-017-1349-x.